Plant protein reduces serum cholesterol levels in hypercholesterolemia hamsters by modulating the compositions of gut microbiota and metabolites - Li-Tao Tong (Elsevier, 2021)
Summary: Plant proteins exert effects of reducing cardio-cerebrovascular disease-related mortality partly via cholesterol-lowering, which was associated with gut microbiota. Here, we verify that there are significant differences in cholesterol levels among hamsters consuming different proteins. The decisive roles of gut microbiota in regulating host cholesterol are illustrated by the fact that the difference in serum cholesterol levels between hamsters feeding with pea protein and pork protein disappeared when treated with antibiotics. The results of cross-over intervention of pea and pork protein show that serum cholesterol levels are reversed with dietary exchange. The corresponding changes in microbiota suggest that Muribaculaceae are responsible for the inhibitory effect of pea protein on serum cholesterol level, whereas the opposite effect of pork protein is due to Erysipelotrichaceae. Moreover, pea protein supplement alters cecal metabolites including arginine/histidine pathway, primary bile acid biosynthesis, short-chain fatty acids, and other lipid-like molecules involved in cholesterol metabolism.